Um estudo historiográfico sobre a psicanálise com crianças no contexto universitário - Silva, Iúri Yrving Müller [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Child Psychoanalysis starts its journey in Europe in the early twentieth century, marked by the pioneering contributions of Melanie Klein and Anna Freud. In Brazil, this type of psychoanalytic service began to be widespread from the 1930s and ended up spreading in well-structured institutional practices, culminating in significant theoretical production. Futhermore, under the auspices of Psychoanalysis Societies, this branch of psychoanalytic science has found greater resonance to its implementation, dissemination, training of child analysts and theoretical work which, though not bulky, has been highly significant. Similarly, academia, through its scientific production, is devoting greater attention to understanding the influences that psychoanalysis has on the way we approach the subject, which has been present in Psychology courses since they were inaugurated in 1960. Since the 1980s, we can observe an auspicious phenomenon, the reception of psychoanalysis by graduate courses in various universities. Therefore, the university encouraged the growth of theoretical literature on the topic, for it didn't aim at a strict analytic training, but at representing a more neutral environment, better able to stimulate and to accept the myriad of points of view than the psychoanalytic institution. Through the analysis of theses and dissertations produced in graduate courses in psychology over the past decade, this research aims at investigating the psychoanalytic theoretical work on children in the twenty-first century, basing on the academic scientific production of that period. Taking the contextual historical method as a reference, the research initially consisted of a bibliographical survey on the topic in national dissertations and theses, from 2000 to 2010. Basing on the results, four categories have been defined, considering the nature of the work: conceptual, psychoanalysis with children...

A Psicanálise com Crianças inicia seu percurso na Europa no início do século XX, marcado pelas contribuições pioneiras de Melanie Klein e Anna Freud. No Brasil, essa modalidade de atendimento psicanalítico começou a ser difundida a partir da década de 1930 e acabou se disseminando em práticas institucionais bem estruturadas, culminando em produção teórica expressiva. E, sob os auspícios das Sociedades de Psicanálise, esse ramo da ciência psicanalítica encontrou maior ressonância para sua aplicação, divulgação, formação de analistas infantis e produção teórica que, apesar de não vultosa, tem se mostrado altamente expressiva. De forma análoga, o meio universitário, por intermédio de sua produção científica, vem devotando maior atenção à compreensão das influências que a psicanálise exerce sobre a maneira de abordamos esse tema, já presente nos cursos de Psicologia desde que foram inaugurados, na década de 1960. A partir dos anos 1980, podemos observar um fenômeno alvissareiro, a acolhida da psicanálise pelos cursos de pós-graduação em diversas universidades brasileiras. Dessa forma, a universidade fomentou a produção teórica sobre o tema, por não visar à formação analítica stricto sensu e representar um ambiente mais neutro, mais apto a estimular e a aceitar a miríade de pontos de vista, do que a instituição psicanalítica. Por meio da análise de dissertações e teses produzidas em cursos de pós-graduação em psicologia na última década, a presente pesquisa tem por objetivo investigar a produção teórica psicanalítica com crianças no século XXI, a partir da produção científica acadêmica. Tomando como referência o método histórico contextual, a pesquisa consistiu inicialmente em um levantamento bibliográfico sobre o tema em dissertações e teses nacionais, no período de 2000 a 2010. A partir dos resultados, foram definidas quatro...
Keywords: Psicanalise infantil; Psicanálise - História; Psicoterapia infantil; Universidades e faculdades - Brasil; Child psychotherapy